Treading softly : paths to ecological order - Princen, Thomas, 1951- (MIT Press, 2010)
"We are living beyond our means, running up debts both economic and ecological, consuming the planet's resources at rates not remotely sustainable. But it's hard to imagine a different way. How can we live without cheap goods and easy credit? How can we consume without consuming the systems that support life? How can we live well and live within our means? In Treading Softly, Thomas Princen helps us imagine an alternative. We need, he says, a new normal, a new ecological order that is actually economical with resources, that embraces limits, that sees sustainable living not as a "lifestyle" but as a long-term connection to fresh, free-flowing water, fertile soil, and healthy food." "That economies must grow is a fundamental belief among economists, politicians, and journalists. But it is rampant material growth that has brought us to this precipice. Princen argues that it is time to build an economy that is grounded in the way natural systems work; that operates as if we have just the right amount of resources rather than endless frontiers. The goal would be to live well by living well within the capacities of those resources. Society's material foundations would be grounded in the biophysical, its practices based on satisfying work, self-reliance, and restraint rather than the purchasing of goods. Princen doesn't offer a quick fix - there's no list of easy ways to save the planet to hang on the refrigerator. He gives us instead a positive, realistic sense of the possible, with an abundance of examples, concepts, and tools for imagining, then realizing, how to live within our biophysical means."--Jacket.